Social and psychological mechanisms of brand communication influence on consumer’s perception - Gomolska, Lily (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article presents the results of research on brand image in customers’ perception, which is being formed in brand communication process under the influence of the corresponding social and psychological mechanisms. It shows that brand communication is a set of specific actions in social interaction process (interpersonal, intergroup, mass-scale) that influence opinion, motives, attitudes and behaviour of consumers towards certain companies, their products and (or) services. The result of brand communication is the image of brand as a social object. The article presents social and psychological model of effective brand communication, the main element of which is the interaction of brand communicator (goods manufacturer/service producer) and recipient (consumer), aimed at exchange of messages about the brand on different channels and "access points". It also highlights interrelations between social-psychological mechanisms of brand communicator’s influence on consumer (conviction, infusion, exposure and imitation) and mechanisms of brand establishment and its functioning in consumer’s perception (social comparison, identification, social categorization, stereotyping, emotional experience and assessments, personalization, self-presentation, self-verification, goal-setting, etc.). It outlines the prospects for further research, which lies in empirical study of social and psychological mechanisms that provide the formation of brand image components according to certain criteria and, consequently, the effectiveness of brand communications.